Adaptation of postural recovery responses to a vestibular sensory illusion in individuals with Parkinson disease and healthy controls. (October 2017) - Lester, Mark E.; Cavanaugh, James T.; Foreman, K. Bo; Shaffer, Scott W.; Marcus, Robin; Dibble, Leland E.
Abstract: Background: The ability to adapt postural responses to sensory illusions diminishes with age and is further impaired by Parkinson disease. However, limited information exists regarding training-related adaptions of sensory reweighting in these populations. Methods: This study sought to determine whether Parkinson disease or age would differentially affect acute postural recovery or adaptive postural responses to novel or repeated exposure to sensory illusions using galvanic vestibular stimulation during quiet stance. Findings: Acutely, individuals with Parkinson disease demonstrated larger center of pressure coefficient of variation compared to controls. Unlike individuals with Parkinson disease and asymptomatic older adults, healthy young adults acutely demonstrated a reduction in Sample Entropy to the sensory illusion. Following a period of consolidation Sample Entropy increased in the healthy young group, which coincided with a decreased center of pressure coefficient of variation. Similar changes were not observed in the Parkinson disease or older adult groups. Interpretation: Taken together, these results suggest that young adults learn to adapt to vestibular illusion in a more robust manner than older adults or those with Parkinson disease. Further investigation into the nature of this adaptive difference is warranted. Highlights: Postural control following galvanic vestibular stimulation is decreased in Parkinson Disease Adaptive responses to repeated vestibular illusion diminish with age and Parkinson Disease Age and Parkinson Disease produce postural control changes with altered temporal structure